Nucleus Accumbens Functional Connectivity with the Frontoparietal Network Predicts Subsequent Change in Body Mass Index for American Children - Assari, Shervin; Boyce, Shanika; Bazargan, Mohsen (Brain sciences, 2020)
Background: Nucleus accumbens (NAc) is a brain structure with a well-established role in the brain reward processing system. Altered function of the NAc is shown to have a role in the development of food addiction and obesity. However, less is known about sex differences in the role of NAc function as a predictor of children’s change in body mass index (BMI) over time. Aim: We used the Adolescent Brain Cognitive Development data (version 2.01) to investigate sex differences in the predictive role of the NAc functional connectivity with the frontoparietal network on children’s BMI change over a one-year follow-up period. Methods: This 1-year longitudinal study successfully followed 3784 9–10-year-old children. Regression models were used to analyze the data. The predictor variable was NAc functional connectivity with the frontoparietal network measured using resting-state functional magnetic resonance imaging (fMRI). The primary outcome was BMI at the end of the 1-year follow up. Covariates included race, ethnicity, age, socioeconomic factors, and baseline BMI. Sex was the effect modifier. Results: NAc functional connectivity with the frontoparietal network was predictive of BMI changes over time. This association remained significant above and beyond all covariates. The above association, however, was only significant in female, not male children. Conclusion: The epidemiological observation that NAc functional connectivity is associated with BMI changes in children is an extension of well-controlled laboratory studies that have established the role of the NAc in the brain reward processing. More research is needed on sex differences in the brain regions that contribute to childhood obesity.